2020
DOI: 10.1101/2020.04.30.071126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experience-dependent inhibitory plasticity is mediated by CCK+ basket cells in the developing dentate gyrus

Abstract: Early postnatal experience shapes both inhibitory and excitatory networks in the hippocampus. However, the underlying circuit plasticity is unclear. Using an enriched environment (EE) paradigm, we assessed the circuit plasticity of inhibitory cell-types in the hippocampus. We found that cholecystokinin (CCK)-expressing basket cells strongly increased somatic inhibition on the excitatory granular cells (GC) following EE while another pivotal inhibitory cell-type, parvalbumin (PV)-expressing cells did not show c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Additionally, the change between the two groups for SF and R metrics argues that the computation can be tuned by experience-dependent mechanisms. EE induces an increased excitatory and inhibitory drive in the DG circuit [ 1 , 3 ]. The increased excitatory drive can in turn reduce the sparsification of the signal in the DG by increasing the activity of the GC in response to EC imputs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the change between the two groups for SF and R metrics argues that the computation can be tuned by experience-dependent mechanisms. EE induces an increased excitatory and inhibitory drive in the DG circuit [ 1 , 3 ]. The increased excitatory drive can in turn reduce the sparsification of the signal in the DG by increasing the activity of the GC in response to EC imputs.…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear, however, whether and to what extent these synaptic alterations support the tuning of the computational processes performed within a circuit. Using the enrichment housing paradigm in which juvenile mice are raised in large cages with toys, a running wheel, and diverse objects, we have recently shown that the experience-dependent plasticity of the hippocampal synaptic network is not homogeneous but rather affects specific microcircuits [ 3 ]. In the dentate gyrus (DG) of mice raised in an enriched environment (EE), we found a robust increase in the inhibitory drive onto principal excitatory cells which was primarily mediated by the addition of somatic GABAergic synapses from the cholecystokinin expressing (CCK +) interneurons (IN) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations